Mauritius : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper and Statistical Appendix discusses initial performance and other issues relating to the implementation of the value-added tax in Mauritius in 1998. The paper highlights that as the Mauritius economy has continued to expand at a relatively rapid pace, the need for the monetary authorities to enhance their ability to influence domestic liquidity, as well as to ensure the integrity of the banking system, has become increasingly apparent. The paper also analyzes various issues in the banking sector of Mauritius.